Photo elicitation: reflecting on multiple sites of meaning. Issue 3 (3rd July 2017) - Dockett, Sue; Einarsdottir, Johanna; Perry, Bob
ABSTRACT: Changing perspectives of children and recognition of the importance of researching with, rather than on, children, have contributed to a great deal of interest in participatory research methods. While many participatory methods have been developed to incorporate visual elements, uncertainty remains about the role and purpose of the image within these. For example, how are images to be analysed; does the image represent a child's 'reality'; is the image itself considered data, or is the major purpose of the image to stimulate discussion? In this paper, we explore the method of photo elicitation and propose the use of critical visual methodology as one means to interrogate the images involved. Using two photos, we reflect on issues of production, content, audience and interpretation and how these contribute to understandings of the visual elements of photo elicitation. Our aim is to support critical reflection and conversation about what has been a widely adopted method in research with young children.